Prepare, Do, Review: A skills‐based approach for laboratory practical classes in biochemistry and molecular biology. Issue 3 (6th May 2016) - Arthur, Peter; Ludwig, Martha; Castelli, Joane; Kirkwood, Paul; Attwood, Paul
Abstract: A new laboratory practical system is described which is comprised of a number of laboratory practical modules, each based around a particular technique or set of techniques, related to the theory part of the course but not designed to be dependent on it. Each module comprises an online recorded pre‐lab lecture, the laboratory practical itself and a post‐lab session in which students make oral presentations on different aspects of the practical. Each part of the module is assessed with the aim of providing rapid feedback to staff and students. Each laboratory practical is the responsibility of a single staff member and through this "ownership, " continual review and updating is promoted. Examples of changes made by staff to modules as a result of student feedback are detailed. A survey of students who had experienced both the old‐style laboratory course and the new one provided evidence of increased satisfaction with the new program. The assessment of acquired shills in the new program showed that it was much more effective than the old course. © 2016 by The International Union of Biochemistry and Molecular Biology, 44:276–287, 2016.